To find the centroid of a triangle given its vertices, we use the formula for the centroid \((G)\) which is the average of the coordinates of the vertices. The formula is:
\[ G\left( \frac{x_1 + x_2 + x_3}{3}, \frac{y_1 + y_2 + y_3}{3} \right) \]
Given the vertices of the triangle are \((2, 3)\), \((-3, -1)\), and \((2, -1)\), we can plug in these coordinates into the formula.
- \(x_1 = 2\), \(y_1 = 3\)
- \(x_2 = -3\), \(y_2 = -1\)
- \(x_3 = 2\), \(y_3 = -1\)
Now calculate the coordinates of the centroid:
\[ G_x = \frac{2 + (-3) + 2}{3} = \frac{2 - 3 + 2}{3} = \frac{1}{3} \]
\[ G_y = \frac{3 + (-1) + (-1)}{3} = \frac{3 - 1 - 1}{3} = \frac{1}{3} \]
Thus, the centroid of the triangle is:
\[ \text{centroid} = \left( \frac{1}{3}, \frac{1}{3} \right) \]
So, the final answer is:
\[ \text{centroid} = \left( \frac{1}{3}, \frac{1}{3} \right) \]